2008
DOI: 10.2169/internalmedicine.47.1127
|View full text |Cite
|
Sign up to set email alerts
|

Facial Angiofibroma as an Initial Manifestation in Multiple Endocrine Neoplasia Type 1

Abstract: F i g u r e 1 . A: a s ma l l f a c i a l a n g i o f i b r o ma f o u n d i n t h e p a t i e n t . B -D: a n g i o f i b r o ma s s e e n i n o t h e r p a t i e n t s wi t h ME N1. Al l p a t i e n t s a r e J a p a n e s e a n d t h e y a l l h a v e h e t e r o z y g o u s g e r ml i n e mu t a t i o n i n t h e ME N1 g e n e . B : 6 4 -y e a r -o l d wo ma n ; C: 6 1 -y e a r -o l d ma n ; D: 7 2 -y e a r -o l d wo ma n . PICTURES IN CLINICAL MEDICINE Facial Angiofibroma as an Initial Manifestation in Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…In MEN1, the most frequent location is facial, mainly the upper lip, in contrast with tuberous sclerosis, where this location is spared [ 76 , 78 ]. Angiofibromas were the most frequent cutaneous tumor observed and were found in 18 studies according to our research [ 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 70 ]. Angiofibromas in MEN1 patients are reported with a frequency between 11% and 88% on studies of different sample size (varying from 145 to 5 patients) [ 48 , 49 , 69 ] ( Table 2 ).…”
Section: Men1 and Skin Tumor Profilesupporting
confidence: 53%
See 1 more Smart Citation
“…In MEN1, the most frequent location is facial, mainly the upper lip, in contrast with tuberous sclerosis, where this location is spared [ 76 , 78 ]. Angiofibromas were the most frequent cutaneous tumor observed and were found in 18 studies according to our research [ 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 70 ]. Angiofibromas in MEN1 patients are reported with a frequency between 11% and 88% on studies of different sample size (varying from 145 to 5 patients) [ 48 , 49 , 69 ] ( Table 2 ).…”
Section: Men1 and Skin Tumor Profilesupporting
confidence: 53%
“…The most common cutaneous tumors found in patients with MEN1 were angiofibromas, collagenomas, and lipomas. Other cutaneous tumors found were melanomas, atypical nevi, basocellular carcinoma, squamous cell carcinoma, acrochordons, papillomatosis confluens et reticularis, gingival papules, and cutaneous T-cell lymphoma of the eyelid, but this category is not sustained by well-designed clinical studies and genetic workup in most cases, thus the association might be incidental ( Table 1 ) [ 31 , 39 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Men1 and Skin Tumor Profilementioning
confidence: 99%
“…She had no other signs of TS and the authors suggested the skin lesions might represent an uncommon response to the defect in tumor suppression due to the NF2 mutation. Angiofibromas have also been reported in a patient with the Birt–Hogg–Dubé (BHD)/Hornstein–Knickenberg syndrome of renal tumors, spontaneous pneumothoraces, and skin tumors that are usually fibrofolliculomas, trichodiscomas, and acrochordons [Schaffer et al, 2005]. In that case the lesions, which numbered over 100, fit the description of facial papules and did not appear until the patient was 38 years old.…”
Section: Discussionmentioning
confidence: 89%
“…In one family angiofibroma appears to have been the only confirmed skin lesion. Thus, it is possible that what is interpreted as angiofibroma may rarely be the sole skin manifestation of BHD but these lesions show later onset in keeping with the fibrous papule form [Schaffer et al, 2005; Toro, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Usually multiple and tending to be more commonly identified with increasing age in MEN1 patients ( 13 15 ), these dermatological manifestations can also be diagnosed in children ( 17 19 ) ( Figure 1 ). In fact, they can be the earliest or only manifestation of MEN1 ( 13 , 17 , 20 23 ). Like other MEN1 manifestations, there is no clear genotype-phenotype correlation ( 24 , 25 ).…”
Section: Cutaneous Tumors (Angiofibromas and Collagenomas)mentioning
confidence: 99%